2017
DOI: 10.1002/gcc.22502
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factors—Intricate players of the bone morphogenetic protein signaling pathway

Abstract: Bone morphogenetic proteins (BMPs) are a family of growth factors, some of which are known by the name growth and differentiation factor (GDF). BMPs were discovered in the 1960s in an attempt to find factors capable of inducing bone formation. By the end of 1980s, several different

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 123 publications
(201 reference statements)
0
5
0
Order By: Relevance
“…An unbiased search for signalling pathways using the Reactome pathway database (Reactome Version 70) (Fabregat et al , 2018) contained the term “SMAD2/SMAD3:SMAD4 heterotrimer regulates transcription” (Fig 9A) as significantly upregulated in DIE astrocytes, with Sp1 , Smad7 , Ccnt2 showing higher expression in these astrocytes. Smads are TFs acting as down‐stream effectors in TGFβ or/and BMP signalling (Luo, 2017; Ampuja & Kallioniemi, 2018; Dituri et al , 2019), and both of these signalling pathways regulate NSC properties, including quiescence (Mira et al , 2010) as well as astrocyte differentiation during development (Mabie et al , 1997; Stipursky et al , 2014). Smad4, a common TGFβ/BMP signalling mediator, is expressed across all DIE astrocyte clusters (Fig 9B).…”
Section: Resultsmentioning
confidence: 99%
“…An unbiased search for signalling pathways using the Reactome pathway database (Reactome Version 70) (Fabregat et al , 2018) contained the term “SMAD2/SMAD3:SMAD4 heterotrimer regulates transcription” (Fig 9A) as significantly upregulated in DIE astrocytes, with Sp1 , Smad7 , Ccnt2 showing higher expression in these astrocytes. Smads are TFs acting as down‐stream effectors in TGFβ or/and BMP signalling (Luo, 2017; Ampuja & Kallioniemi, 2018; Dituri et al , 2019), and both of these signalling pathways regulate NSC properties, including quiescence (Mira et al , 2010) as well as astrocyte differentiation during development (Mabie et al , 1997; Stipursky et al , 2014). Smad4, a common TGFβ/BMP signalling mediator, is expressed across all DIE astrocyte clusters (Fig 9B).…”
Section: Resultsmentioning
confidence: 99%
“…25 MH2 domains are expressed in all eight Smads and are responsible for interaction with BMP receptors, interaction with DNA-binding proteins, and transcriptional activation. 25 Many transcription factors have been identified that regulate BMP target genes, although further work is needed to establish if these are universal regulators of BMP signaling or context-dependent in their mode of action, as reviewed in detail by Ampuja et al 26 For example, the transcription factor ATF2 was shown to activate the promoter of β-myosin heavy chain, important in cardiac development. 27 Several pathways have also been identified that signal in a Smad-independent manner (Figure 1), known as noncanonical pathways.…”
Section: Canonical and Noncanonical Pathwaysmentioning
confidence: 99%
“…Bone morphogenetic proteins (BMPs), included in the transforming growth factor beta (TGFβ) superfamily, are involve from embryogenesis to adult organ cell homeostasis [1][2][3][4][5]. Initially described in bone formation [6], this protein group is divided into at least four subgroups with similar functions and biochemical structures [2].…”
Section: Introductionmentioning
confidence: 99%